Esophageal Mucoepidermoid Carcinoma: A Review of 58 Cases - Wang, Xin; Chen, Yu-ping; Chen, Shao-bin (Frontiers in Oncology, 2022)
Background: Esophageal mucoepidermoid carcinoma (EMEC) is a rare disease. The biological behavior and treatment of this malignancy are not well established. Methods: Data from 58 patients with EMEC who underwent esophagectomy were retrospectively analyzed and compared with 5028 patients with esophageal squamous cell carcinoma (ESCC). Kaplan–Meier and multivariate Cox regression analyses were conducted to investigate the association between clinicopathological factors and survival. Results: The study cohort included 36 males and 22 females with a median age of 59 years (range, 40-78 years). Of the 47 patients who underwent preoperative esophagoscopic biopsy, only 1 patient was diagnosed with EMEC. EMEC was more often found in female patients (39.7% versus 25.8%, P=0.036) and patients with EMEC had a significantly lower rate of lymph node metastasis (25.0% versus 49.4%, P<0.001) than patients with ESCC. After 1:1 propensity score matching, the 5-year overall survival rate of 55.2% for patients with EMEC was similar to that of 61.9% for patients with ESCC (P=0.399). Conclusions: EMEC is a rare disease that more often affects females and these patients has less lymph node metastasis than patients with ESCC. Preoperative esophagoscopic biopsy has difficulty obtaining an accurate pathological diagnosis for EMEC patients. The prognosis for EMEC is similar to that for ESCC.